Factors affecting successful mobilization with plerixafor: an Italian prospective survey in 215 patients with multiple myeloma and lymphoma. Issue 2 (19th June 2013) - Lanza, Francesco; Lemoli, Roberto M.; Olivieri, Attilio; Laszlo, Daniele; Martino, Massimo; Specchia, Giorgina; Pavone, Vincenzo; Imola, Manuela; Pasini, Annalisa; Milone, Giuseppe; Scortechini, Ilaria; Todisco, Elisabetta; et al.
<x xml:space="preserve">Abstract</x> Background Although the efficacy of plerixafor in peripheral blood stem cell (PBSC) mobilization has been explored in several studies, factors associated with successful plerixafor mobilization after administration of granulocyte–colony‐stimulating factor (G‐CSF), with or without chemotherapy, have not been investigated. We analyzed data on PBSC mobilization from a large Italian database of lymphoma and myeloma plerixafor‐treated patients. Study Design and Methods Two endpoints were established to define successful mobilization: patients with at least 2 × 106 CD34+ cells/kg collected by three leukapheresis procedures and patients achieving a peak count of at least 20 × 106 CD34+ cells/L during mobilization. Results Plerixafor achieved successful mobilization in both predicted (n = 64) and proven poor mobilizers (PMs; n = 143), classified according to the Gruppo Italiano Trapianto di Midollo Osseo (GITMO) criteria. Successful mobilization was independent of type of mobilization (steady state or chemotherapy); age; sex; disease; number or type of chemotherapy regimens preceding plerixafor; radiation therapy; prior treatment with melphalan, carmustine, lenalidomide, and radioimmune conjugates; and laboratory variables. Multivariate analysis identified previous fludarabine treatment and premobilization platelet count as predictors of successful mobilization. Conclusion This large, prospective, nationwide study confirmed plerixafor efficacy for mobilizing PBSCs when added to G‐CSF with or without chemotherapy. Plerixafor can overcome negative effects of most predictors of poor mobilization to achieve satisfactory harvest both in predicted and proven PM.